2014
DOI: 10.4194/1303-2712-v14_2_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Antioxidant defense system and oxidative stress biomarkers were determined in the liver tissue from males and females of sea trout (Salmo trutta m. trutta L.) affected by Aeromonas hydrofila infection causing ulcerative dermal necrosis (UDN) syndrome. Histological results from hepatic parenchyma in UDN-affected trout show that cytoplasmic vacuolation of hepatocytes, loss of normal basophilia by cytoplasm, presence of pigment deposition in the parenchyma are a signs of liver deterioration. Impaired circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…•− levels in combination with decreased SOD activity. A study with brown trout (Salmo trutta trutta) showed that infection with A. hydrophila reduced the activity of SOD and CAT enzymes [110]. In this investigation, we observed significant interactions between the effects of dietary supplementation with R-(+)-limonene and A. hydrophila infection on O 2…”
Section: Discussionsupporting
confidence: 45%
“…•− levels in combination with decreased SOD activity. A study with brown trout (Salmo trutta trutta) showed that infection with A. hydrophila reduced the activity of SOD and CAT enzymes [110]. In this investigation, we observed significant interactions between the effects of dietary supplementation with R-(+)-limonene and A. hydrophila infection on O 2…”
Section: Discussionsupporting
confidence: 45%
“…The detrimental impact of bacterial infections on the organism's tissues is partly associated with the promotion of oxidative stress [119]. The flavonoids present in the plants provide a beneficial antioxidant effect through their capability of scavenging the ROS and consequently reducing their harmful effects [120].…”
Section: Discussionmentioning
confidence: 99%
“…The first UDN outbreak was reported in Scotland, dated 1820, thus in the heart of the Industrial Revolution period (1733 -1913) (Grimble, 1899). The number of UDN cases is still growing in Europe (Figure 2) (Munro, 1970;Ljungberg and Johansson, 1977;Meier et al, 1977;Lounatmaa and Janatuinen, 1978;Johansson et al, 1982;Larsen and Jensen, 1982;Eiras and Saraiva, 1988;Roberts, 1993;Law, 2001;Kurhalyuk et al, 2009;Grudniewska et al, 2011;Kazuńet al, 2011;Kurhalyuk et al, 2011;Grudniewska et al, 2012;Grawiński and Kozińska, 2013;Tkachenko et al, 2014;Ciepliński et al, 2018). The first report of UDN for the Baltic region indicates the first occurrence in 1972 (Roberts, 1993), while the first significant outbreak of UDN in the Słupia River occurred in 2007 (Ciepliński et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the variability of temperature may be reflected in the dynamics of the pH difference between the river and the sea (Figure 3). The changing environmental conditions, including acid-base water properties, may cause detrimental effects and diseases in fish not acclimatized to new The map of the UDN occurrence (Grimble, 1899;Munro, 1970;Ljungberg and Johansson, 1977;Meier et al, 1977;Lounatmaa and Janatuinen, 1978;Johansson et al, 1982;Larsen and Jensen, 1982;Eiras and Saraiva, 1988;Roberts, 1993;Law, 2001;Kurhalyuk et al, 2009;Grudniewska et al, 2011;Kazuńet al, 2011;Kurhalyuk et al, 2011;Grudniewska et al, 2012;Grawiński and Kozińska, 2013;Tkachenko et al, 2014;Ciepliński et al, 2018). The inserts show the number of UDN-oriented publications by year and by country (Scopus).…”
Section: Resultsmentioning
confidence: 99%